"Take a Break!": A Qualitative Study of Shift-Duty Police Officers' On-The-Job Breaks. (March 2023) - Toh, Shi Min; Cho, Eunae
This qualitative study examined on-the-job breaks taken by shift-duty police officers. We explored the nature of on-the-job breaks among officers, their perception of these breaks as helping them to recover and replenish resources, and what factors shaped their on-the-job breaks. Data were collected from 21 shift-duty police officers via semi-structured interviews. Findings show that on-the-job breaks were categorized into official and unofficial breaks, each of which had fairly distinctive characteristics. The timing, activities engaged in during breaks, and subjective experiences during breaks were thought to determine the effectiveness of on-the-job breaks. Officers reported that the adverse impacts of skipping a break tended to exceed the benefits of taking a break. On-the-job breaks were shaped by various work and non-work factors. As the first study delving into on-the-job breaks among shift-duty police officers, this study expands our understanding of specific strategies employed by police officers to deal with ongoing work demands.